Investigating Properties of Interlocking Bricks with Rubber Glove Manufacturing Residue (RGMR) and Crumb Rubber. - SOO , SIN QUAN (Universiti Teknologi PETRONAS, 2020)
Brick is one of the most important materials in the construction industry due to its awesome durability and aesthetic appearances. However, there are drawbacks to it, whereby the production of conventional burnt clay bricks consumes lots of natural resources and released plenty of greenhouse gases into the atmosphere. Yet, the construction of the conventional masonry wall is highly dependent on manpower and the interlocking bricks with the key and lock features were introduced to overcome the flaws of conventional bricks. Next, the rubber glove is a vital member in many sectors, especially in the medical and healthcare sector. The demand for the rubber glove had increased significantly in the year 2020 due to the COVID-19 virus breakout. The manufacturing process of rubber glove produces a high amount of effluent that contains a high concentration of BOD, which results in the generation of Rubber Glove Manufacturing Residue (RGMR) after the effluent treatment by coagulation process. The recycling of RGMR is still limited although the RGMR is abundant.